2022
DOI: 10.1038/s41524-021-00678-3
|View full text |Cite
|
Sign up to set email alerts
|

Design high-entropy carbide ceramics from machine learning

Abstract: High-entropy ceramics (HECs) have shown great application potential under demanding conditions, such as high stresses and temperatures. However, the immense phase space poses great challenges for the rational design of new high-performance HECs. In this work, we develop machine-learning (ML) models to discover high-entropy ceramic carbides (HECCs). Built upon attributes of HECCs and their constituent precursors, our ML models demonstrate a high prediction accuracy (0.982). Using the well-trained ML models, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 71 publications
0
47
0
Order By: Relevance
“…Interestingly, ML models are available to forecast the entropy‐forming ability for rationally designing high‐entropy ceramic carbides based on DFT, and two well‐trained models − artificial neural network (ANN) and support vector machine (SVM) − have been used satisfactorily to screen the feasible elemental combinations. [ 107 ]…”
Section: A Marriage Between Hem Catalysts and Electrochemical Water S...mentioning
confidence: 99%
“…Interestingly, ML models are available to forecast the entropy‐forming ability for rationally designing high‐entropy ceramic carbides based on DFT, and two well‐trained models − artificial neural network (ANN) and support vector machine (SVM) − have been used satisfactorily to screen the feasible elemental combinations. [ 107 ]…”
Section: A Marriage Between Hem Catalysts and Electrochemical Water S...mentioning
confidence: 99%
“…The ML method achieves simulations with comparable accuracy and exhibits better flexibility in the dynamic nature of phase formation and stability than the conventional DFT method. [39] This model has been developed to explore and predict material composition, phase formation, mechanical property, and application performance in the past few years. [40] Zhang et al reported ML models to evaluate the single-phase probability of 90 possible high entropy carbide ceramics (HECCs) composed of group IV-VI metals.…”
Section: Machine Learningmentioning
confidence: 99%
“…[40] Zhang et al reported ML models to evaluate the single-phase probability of 90 possible high entropy carbide ceramics (HECCs) composed of group IV-VI metals. [39] The designed models combined with the preliminary DFT results screened 38 single-phase HECCs with high prediction accuracy (0.982). Furthermore, the group revealed that the valence electron concentration (VEC) deviations and the electronegativity deviations of the constituents were critical factors for the phase formation of HECC.…”
Section: Machine Learningmentioning
confidence: 99%
“…This finding opened a kind of “wild west” for ceramists currently racing to discover new materials taking advantage of both experimental and analytical approaches. 9,33,34…”
Section: Introductionmentioning
confidence: 99%
“…This nding opened a kind of "wild west" for ceramists currently racing to discover new materials taking advantage of both experimental and analytical approaches. 9,33,34 Of special interest are high-entropy oxides (HEO) with rock salt structures. In particular, alkali-doped rock salts in the MgO-CoO-NiO-CuO-ZnO system have shown surprising electrochemical and dielectric properties, including giant dielectric constant, 35 catalytic 36 and electrocatalytic activity, 37 Lisuperionic conductivity 38 and high Li-storage capacity.…”
Section: Introductionmentioning
confidence: 99%